Short-step syntheses of naturally occurring polyoxygenated aromatics based on site-selective transformation. Issue 7 (3rd July 2017) - Yamashita, Yasunobu; Biard, Alan; Hanaya, Kengo; Shoji, Mitsuru; Sugai, Takeshi
Abstract: Wogonin and astringin were synthesized from inexpensive chrysin and piceid in short steps. The key feature of these syntheses is site-selective transformation. The target molecules were obtained in 27 and 62% yields from the starting materials, respectively. Graphical abstract: : wogonin and astringin were synthesized from chrysin and piceid in short steps, based on site-selective transformations of acetyl protective groups.